Die lustige Witwe and the Creation of the Silver Age of Viennese Operetta. (10th July 2014) - Baranello, Micaela
Abstract: Franz Lehár's Die lustige Witwe (1905) was conceived during a period of instability in both operetta and Viennese life. Considering the music and reception of both Witwe and some of its immediate, now-forgotten predecessors, this article argues that the operetta's dramatic and musical dualism between urbane, Offenbach-like Paris and folksy, imaginary Pontevedro can be read both as a response to operetta's conflicting priorities of satire and sentiment and as a depiction of the multi-ethnic world of working-class Vienna. The operetta's unusual popularity, subsequent influence and exceptionally long performance history have tended to obscure these more immediate concerns.